Bioconversion of Plastic Waste into Compost Using Frass from Zophobas atratus and Tenebrio molitor: A Sustainable Approach for Brassica rapa L. Growth - Muhammad Al-Irsyad; Nurnaningsih Herya Ulfah; Anita Sulistyorini; Melati Nastiti Ningrum Abidin; Shohifatul Ilma; Anu Surach (Universitas Airlangga, 2026)
Introduction: Ultra-slow degradation makes LDPE a major source of environmental pollutant. Considering the global annual plastics consumption is in the range of 0.5 to 1 trillion units, there is a pressing need to understand the environmental and health effects of plastics and particularly those of LDPE. The study is based on the exploration of biologically converted LDPE by superworms (Zophobas atratus) and mealworms (Tenebrio molitor) and the application of the frass of these worms as a liquid biofertilizer for plant growth. Methods: This study was carried out using an experimental design of zero-waste vermicomposting. To monitor N retention at larva survival, frass production and nutrients in frass (N-P-K and carbon balance), worms were fed with either organic feed (pollard) or LDPE plastic. Subsequently, vermicompost of tea was prepared from the frass and applied as a fertilizer in hydroponic cultivation of Brassica rapa L. (bok choy) for determining the growth performance using specific quantitative traits including height, leaf number, and root length. Results and Discussion: There were no significant differences in nutrient composition either between the worm castings derived from those fed on plastic and wheat bran or between those fed on plastic and wheat bran. Over the 30 days of growth, bok choy plants fertilized with mealworm-derived vermicompost from plastic feed showed improved the other treatment groups in root growth, plant height, leaf count. Conclusion: Using frass from plastic-fed worms does not negatively impact plant growth. However, adding organic feed is necessary to optimize the nutrient content required by plants.